Efisiensi Bank Umum Syariah Pada Masa Pemulihan Ekonomi Pasca Covid-19 - Lidyana Arifah (Al-bank: Journal of Islamic Banking and Finance, 2023)
This study aims to measure the efficiency level of Islamic Commercial Banks during the economic recovery period after the co-19 storm. The type of research is quantitative descriptive research. The samples in this study were 10 Islamic Commercial Banks. The data collection technique in this study used documentation in the form of Islamic bank financial reports published by OJK. The data analysis technique uses the Data Envelopment Analysis (DEA) method. The results showed that there were differences between the 2 models used, namely CRS and VRS. Based on the CRS model, 5 Islamic commercial banks experienced efficient conditions, while the other 5 banks were inefficient. While using the VRS model only 2 banks did not reach efficient, namely Bank Muamalat Indonesia and Bank Mega Syariah. While the other 8 commercial banks reached the efficient level. Based on these results, some inefficient banks are advised to increase their inputs to help improve bank performance.